A Systematic Review of Longitudinal Studies Investigating the Association Between Early Life Maternal Depression and Offspring ADHD. Issue 9 (July 2022) - Tucker, James R. D.; Hobson, Christopher W.
Objective: The systematic review sought to understand the relationship between maternal depression and later ADHD in children. Method: Three databases were used to identify the studies (Medline, Web of Science and PsychInfo) resulting in 1, 223 studies being screened and 14 articles being included in the review. Results: The majority of studies ( N = 11) reported a significant relationship between maternal depression (across both prenatal and postnatal periods) and ADHD symptoms in children. This relationship remained significant when temperament, or past ADHD symptoms were controlled for. Several methodological issues were identified including; overreliance on maternal report and parental ADHD not being accounted for in most studies. Conclusion: The review adds to the literature regarding the temporal relationship between maternal depression and the development of ADHD in children, and thus supports the case for improving access to mental health services for mothers as a preventative strategy in the development of child psychopathology.